The Role of Demand Factors in Utilization of Professional Care during Childbirth: Perspectives from Yemen. (18th September 2011) - Kempe, Annica; Noor-Aldin Alwazer, Fatoom; Theorell, Töres
Abstract : Background . Utilization of professional care during childbirth by women in low-income countries is important for the progress towards MDG 5. In Yemen, home births have decreased minimally during the past decades. Objective . The study investigates the influence of socio-demographic, birth outcome and demand factors on women's future preference of a home or institutional childbirth. Method . We interviewed 220 women with childbirth experience in urban/rural Yemen. We performed bivariate chi-square tests and multiple logistic regression analysis. A multistage sampling process was used. Results . The issues of own choice, birth support and birth complications were the most important for women's preference of future location of childbirth. Women who had previously been able to follow their own individual choice regarding birth attendance and/or location of childbirth were six times more likely to plan a future childbirth in the same location and women who received birth support four times more likely. Birth complications were associated with a 2.5-fold decrease in likelihood. Conclusions . To offer women with institutional childbirth access to birth support is crucial in attracting women to professional care during childbirth. Yemeni women's low utilization of modern delivery care should be seen in the context of women's low autonomy and status.